2012
DOI: 10.1007/978-1-62703-083-0_26
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Skin and Wound Healing

Abstract: MicroRNAs (miRNAs) are small noncoding RNA molecules ~22 nucleotides in length that can post-transcriptionally repress gene expression. MiRNAs bind to their target messenger RNAs (mRNAs), leading to mRNA degradation or suppression of translation. miRNAs have recently been shown to play pivotal roles in skin development and are linked to various skin pathologies, cancer, and wound healing. Chronic wounds represent a major health burden and drain on resources and developing more effective treatments is therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 47 publications
(62 reference statements)
1
47
0
Order By: Relevance
“…The clinical utility of miRNAs as disease biomarkers has been studied in skin malignancy and has gained the attention of cutaneous fibrosis researchers. MiRNAs regulating skin fibrotic processes, such as let-7a, miRNA-7, miRNA-196a, and miRNA-150, have been detected in decreased levels in the serum of patients with scleroderma and affirm the potential of miRNA as a marker of the disease [3,10,18,23,24,42,69]. One study also demonstrated that serum levels of miRNA-142-3p are significantly higher in scleroderma patients [39].…”
Section: Clinical Applications Of Mirnas In Skin Fibrosismentioning
confidence: 99%
See 3 more Smart Citations
“…The clinical utility of miRNAs as disease biomarkers has been studied in skin malignancy and has gained the attention of cutaneous fibrosis researchers. MiRNAs regulating skin fibrotic processes, such as let-7a, miRNA-7, miRNA-196a, and miRNA-150, have been detected in decreased levels in the serum of patients with scleroderma and affirm the potential of miRNA as a marker of the disease [3,10,18,23,24,42,69]. One study also demonstrated that serum levels of miRNA-142-3p are significantly higher in scleroderma patients [39].…”
Section: Clinical Applications Of Mirnas In Skin Fibrosismentioning
confidence: 99%
“…In combating skin fibrosis, anti-fibrotic miRNAs may be upregulated with the use of miRNA mimics or viral vectors [3,25]. Mimics are synthetic short double-stranded oligonucleotides, consisting of a guide strand and a passenger strand [3,17].…”
Section: Clinical Applications Of Mirnas In Skin Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…It also regulates MMP-2 via the PTEN pathway as a result of myocardial infarction 44 . Inhibition of the PTEN pathway also activates many downstream targets, such as mTOR, which regulates protein synthesis, glucose homeostasis, autophagy, and proliferation (Figure 2).…”
Section: Main Textmentioning
confidence: 99%